Logging in the Andamans - Bhattee, Shamsher Singh (Indian Forester, 1958)
The article gives an account of the various logging operations employed in the past and in the present days for extraction of timber from these islands. The quantity of timber in the early days extracted from these islands was negligible and could be easily extracted with the help of buffaloes and a few labourers. As the demand for Andaman timbers grew, tapping of large areas with better means of exploitation became a necessity. The scattered fellings were replaced by well-organized concentrated fellings and buffalo extraction by elephant extraction and finally by the present day elephant-cum-mechanical extraction. The use of machinery for extraction of timber has greatly increased the outturn. Today the annual production of timber from these islands is between 90,000 to 1,00,000 tons as against about 3,000 tons in 1884-85. The vadous factors affecting the logging methods such as nature at the country, climate, composition and type of forests, management, etc., are also described.